Elastic Modulus and Hardness of Plasma‐Polymerized Organosilicones Evaluated by Nanoindentation Techniques. Issue 9 (22nd June 2015) - Cech, Vladimir; Lukes, Jaroslav; Palesch, Erik; Lasota, Tomas; Fouquet, Thierry; Girard‐Lauriault, Pierre‐Luc
<x xml:space="preserve">Abstract</x> Nanoindentation techniques are today a standard tool for the characterization of mechanical properties of thin films at nanoscale. In this feature article, we introduce various techniques, together with their applications for plasma‐polymerized organosilicones: starting from conventional instrumented nanoindentation, followed by continuous oscillatory loading and cyclic nanoindentation by partial unloading for assessing the depth profile of mechanical properties, to continuous mechanical mapping over the sample surface. Methods of analyzing and interpreting the measured data are presented to determine the elastic modulus and hardness of tested films. Plasma polymer films are materials of viscoelastic or elastic–plastic behavior; the correct technique must therefore be selected to give the most accurate mechanical property measurements. A number of limitations of the techniques are also discussed. A list of conditions for successful analysis of mechanical properties is included.<inline-graphic xlink:href="ark:/27927/pgj2ntc6gxd" content-type="ppap201500036-gra-0001" xlink:type="simple" xmlns:xlink="http://www.w3.org/1999/xlink" />